Prawo właściwe dla zobowiązań deliktowych wynikających z naruszenia zasad ochrony danych osobowych przyjętych w RODO - Świerczyński, Marek (Problemy Prawa Prywatnego Międzynarodowego, 2020)
Disputes arising from international data breaches can be complex. Despite the introduction of new, unified EU regulation on the protection of personal data (GDPR), the European Union failed to amend the Rome II Regulation on the applicable law to non-contractual liability and to extend its scope to the infringements of privacy. GDPR only contains provisions on international civil procedure. However, there are no supplementing conflict-of-law rules. In order to determine the applicable law national courts have to apply divergent and dispersed national codifications of private international law. The aim of this study is to propose an optimal conflict-of-law model for determining the applicable law in case of infringement of the GDPR’s privacy regime.